The Arthroscopic Latarjet Procedure for Anterior Shoulder Instability: 5-Year Minimum Follow-up. (November 2014) - Dumont, Guillaume D.; Fogerty, Simon; Rosso, Claudio; Lafosse, Laurent
Background: The arthroscopic Latarjet procedure combines the benefits of arthroscopic surgery with the low rate of recurrent instability associated with the Latarjet procedure. Only short-term outcomes after arthroscopic Latarjet procedure have been reported. Purpose: To evaluate the rate of recurrent instability and patient outcomes a minimum of 5 years after stabilization performed with the arthroscopic Latarjet procedure. Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent the arthroscopic Latarjet procedure before June 2008 completed a questionnaire to determine whether they had experienced a dislocation, subluxation, or further surgery. The patients also completed the Western Ontario Shoulder Instability Index (WOSI). Results: A total of 62 of 87 patients (64/89 shoulders) were contacted for follow-up. Mean follow-up time was 76.4 months (range, 61.2-100.7 months). No patients had reported a dislocation since their surgery. One patient reported having subluxations since the surgery. Thus, 1 patient (1.59%) had recurrent instability after the procedure. The mean ± standard deviation aggregate WOSI score was 90.6% ± 9.4%. Mean WOSI domain scores were as follows: Physical Symptoms, 90.1% ± 8.7%; Sports/Recreation/Work, 90.3% ± 12.9%; Lifestyle, 93.7% ± 9.8%; and Emotions, 88.7% ± 17.3%. Conclusion: The rate of recurrent instability after arthroscopic Latarjet procedure is low in this series of patients with a minimum 5-year follow-up. Patient outcomes as measured by the WOSI are good.